1995
DOI: 10.1034/j.1600-0501.1995.060104.x
|View full text |Cite
|
Sign up to set email alerts
|

Damping characteristics of bone‐to‐implant interface; A clinical study with the Periotest® device.

Abstract: The Periotest device was used to evaluate the damping characteristics of different bone-to-implant interfaces of Brånemark implants. Implant and abutment lengths were found to have a significant influence on Periotest value (PTV). There was no statistical difference between PTVs of implants located in the anterior and posterior areas of the same jaw at abutment connection. No differences were found between PTVs of standard and self-tapping implants. PTVs at abutment connection were highly influenced by the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 0 publications
2
28
0
1
Order By: Relevance
“…Reported PTVs were lower in the mandible than in the maxilla. The presence of a mandibular cortical layer is likely responsible for this finding, which has been reported in other clinical studies . In the present study, the bone density at the implant sites was evaluated during the initial osteotomy using a small pilot drill.…”
Section: Discussionsupporting
confidence: 63%
“…Reported PTVs were lower in the mandible than in the maxilla. The presence of a mandibular cortical layer is likely responsible for this finding, which has been reported in other clinical studies . In the present study, the bone density at the implant sites was evaluated during the initial osteotomy using a small pilot drill.…”
Section: Discussionsupporting
confidence: 63%
“…One may argue that cadaver studies are biased by the fact that a bone-implant interface after placement does probably respond differently to excitation in a vital, perfused environment than in a bloodless cadaver. Differences in RFA values did not correspond with histomorphometric parameters in an experimental in vivo study 37 and a recently published clinical study failed to show a significant decrease of RFA mean values in failing implants, but there was a significant decrease between clinically stable and rotation mobile implants 35 . In addition, an experimental study in dogs found a correlation between radiographic bone levels and ISQ values 34 .…”
Section: Discussionmentioning
confidence: 47%
“…Hence, there is only indirect evidence that removal torque corresponds to bone-implant contact rate 29 . Experimental results suggest that there is also no obvious link between RFA values and removal torque, as STENPORT et al 37 could not find a difference in removal torque despite differences in RFA values in implants in rabbit tibiae.…”
Section: Discussionmentioning
confidence: 92%
“…Periotest was introduced to measure tooth and implant movement by Schulte et al [28], and was demonstrated to be useful for the assessment of implant stability [29–31]. In our study, the EL implants showed poor stability during abutment placement, but greater stability at 2 and 4 weeks following loading when compared to DL implants by means of PTV.…”
Section: Discussionmentioning
confidence: 53%